(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Accurate and real-time capable mathematical models are essential for the design of optimal model-based control strategies. The optimal operation of wave energy converters (WECs) is one of the key factors for their commercialization and continued reduction of the levelized cost of energy (LCOE). Model-based control schemes, such as model-predictive control, have demonstrated superior performance in achieving the objectives related to WEC operation. Developing an accurate yet real-time capable model suitable for optimal model-based control design can be a challenging task, where a trade-off between model accuracy and complexity must be made for the underlying mathematical model to achieve real-time performance. In this contribution, a systematic modeling framework tailored to the derivation of a control-oriented model for a point-absorber WEC is proposed. This framework allows for the systematic consideration of nonlinear hydrodynamic and power take-off (PTO) forces. It makes use of linear wave and potential flow theory as well as the Euler-Lagrange formalism enabling efficient derivation of kinematic and dynamic equations. Moreover, major parts of the model implementation can be automated utilizing a computer-algebra software. The resulting model is given in time-domain and can serve as basis for optimal model-based control design or fast numerical simulations. The application of the proposed framework is demonstrated based on CorPower Ocean’s point-absorber WEC considering relevant degrees of freedom (DoF) such as heave, roll, and pitch. Numerical simulations are presented, showing the WEC’s response for different model simplifications to highlight the balance between accuracy and computational efficiency. The results demonstrate the effectiveness of the proposed modeling framework in capturing the essential dynamics of the WEC while maintaining computational efficiency. This paper presents a comprehensive approach to the control-oriented modeling of point-absorber WECs. The proposed framework extends results from the literature deriving a control-oriented model while systematically considering nonlinear hydrodynamic and PTO forces as well as several kinematic degrees of freedom. By addressing the trade-off between model accuracy and real-time capability, this framework enables the systematic development of fast numerical simulation models as well as optimal model-based control strategies. The presented simulation results give relevant insights into the WEC’s response considering different levels of simplification. Future work will aim at extending this framework to WEC arrays as well as the application of the control-oriented model in optimal model-based control algorithms.